1.∫sec^2x tan^3x dx
=∫tan^3(x)*d(tan(x));;d(tan(x))=sec^2(x)*dx
=(1/4)*tan^4(x)+C
2.∫sin^2x cos^2x dx
=(1/4)*∫[2sin(x)*cos(x)]^2*dx
=(1/4)*∫sin^2(2x)dx
=(1/8)*∫(1-cos(4x))dx
=(1/8){x-(1/4)*sin(4x)}+C
3.∫sin^5x dx
=-∫sin^4(x)d(cos(x))
=-∫(1-cos^2(x))^2*d(cos(x))
=-∫(1-2(cosx)^2+(cosx)^4)*d(cosx)
=∫(-1+2(cx)^2+(cx)^4)d(cx);;cx=cosx
=-cos(x)+(2/3)*cos^3(x)+(1/5)*cos^5(x)+C
4.∫dx/(9-x^2)^(5/2)
=∫3cos(y)dy/(3cos(y))^5;;y=3sin(x), dy=3cos(y)
=∫dy/(3cos(y))^4
=(1/81)*∫sec^4(y)dy
=(1/81)*∫sec^2(y)d(tan(y))
=(1/81)*∫(1+tan^2(y))d(tan(y))
=(1/81)*{tan(y)+(1/3)*tan^3(y)}+C
=(tan(y)/81)*(1+(1/3)*tan^2(y))+C
5.∫(4x^2-2x-10)dx/[(x+1)(x-1)x]
=∫[a/x+b/(x+1)+c/(x-1)]dx
=∫(10/x-2/(x+1)-4/(x-1))dx
=10*ln(x)-2*ln(x+1)-4*ln(x-1)+ln(c)
=ln{c*x^10/[(x+1)^2*(x-1)^4]}
=ln{cx^10/[(x-1)(x^2-1)]^2}
其中f(x)=2(2x^2-x-5)
=a(x^2-1)+bx(x-1)+cx(x+1)
f(0)=-10=-a => a=10
f(1)=-8=2c => c=-4
f(-1)=-4=2b => b=-2
This entry passed through the Full-Text RSS service — if this is your content and you're reading it on someone else's site, please read the FAQ at fivefilters.org/content-only/faq.php#publishers. Five Filters recommends: 'You Say What You Like, Because They Like What You Say' - http://www.medialens.org/index.php/alerts/alert-archive/alerts-2013/731-you-say-what-you-like-because-they-like-what-you-say.html